Corn Cost-Return Budget in North Central Kansas - Dhuyvetter, Kevin C. (My University, 1997)
This publication provides estimated cost and returns for forward farm planning for corn production in north central Kansas.
MF2161_1997_10
Keywords: MF2161; Crops; Economics; MF